Collaborating across boundaries: Developing a cross-departmental approach to English language development in an undergraduate business unit - Dunworth, Katie; Briguglio, Carmela (Association for Academic Language and Learning, 2010)
This paper analyses a collaborative activity undertaken to identify and support undergraduate students at one Australian university who could be considered "at risk" because of the level of their English proficiency. The program, which was piloted in 2009, involved collaboration among staff across a number of areas: the faculties of Business and Health Sciences, academic language and learning staff and TESOL specialists. The project comprised an initial compulsory English language diagnostic assessment of all students enrolled in a discipline-specific communication skills unit, and the provision of a structured series of supplementary English language tutorials for those who were found to be in need of additional developmental assistance. The procedure, activated under the nomenclature, Starting University Confidently and Competently English Support Scheme (SUCCESS), was linked to the unit in the sense that the supplementary tutorials complemented the content of the disciplinary unit. The pilot program not only revealed the benefits of the scheme for the students and a wider group of stakeholders, but also uncovered some problematic issues that served as lessons for the future and threw up some ongoing questions.